The openness of Muslim youth towards the transformation of Chinese identity through coffee culture - Hidayat, Samsul; Idaman, Idaman; Haiming, Wen (Indonesian Journal of Islam and Muslim Societies, 2025)
This research aims to explore the opennes of the Muslim youth toward the transformation of the Chinese identity through coffee culture and its role in bridging the cross cultural communication and tolerance. Employing qualitative investigation and performing in-depth interviews at Chinese-style coffee shops in Pontianak, Indonesia, this research examines how these places enable the cultural encounter and formation of hybrid identity. Research evidence indicates that Chinese-style coffee shops serve as social meeting places that promote cultural exchange, inter-religious tolerance and cultural diversity. This culture is well accepted by Muslim youth and they adapted to the culture in their own context and in doing so they help in contributing to the shared cultural practices. This research validates the role of social spaces in raising multicultural presence and cross-cultural interaction. This research presents the suggested strategies for increasing diversity and offers ideas for future research on cultural relations in other settings. The research therefore reveals the significance of coffee culture as media to bridge social differences and encourage social inclusion.